-ata nominalisations in Maltese: a language contact perspective (Atti del Sodalizio Glottologico Milanese, 2023)
The -ata derivational suffix is attested frequently in nominalisations in Italo-Romance languages and its functions related to ‘event/single instance’ nouns have been documented extensively. This affix with these functions is also present in the derivational morphology of Maltese, in which diachronic and synchronic developments of -ata nominalisations reflect the evolutionary paths of this language, characterised by contact. By investigating the etymology of verbal and nominal bases, this research provides a classification of forms which take the -ata suffix in Maltese to refer to events and single instances within them, through derivation involving contact with Italian, English and Sicilian base forms. -ata nominalisations resulting from etymologically Arabic bases will also be included in the classification.